Ramsay Hunt Syndrome – Case Report - Ribeiro, Joana Freitas; Gorgulho, Cátia; Matos, Ana; Alves, Tiago (Brazilian Journal of Case Reports, 2025)
Ramsay Hunt Syndrome (RHS) results from the reactivation of the varicella-zoster virus (VZV). Its incidence is approximately 5 per 100,000 people per year. The clinical presentation is variable, with the most common manifestation being ipsilateral facial paralysis, otalgia, and vesicular rash. Several factors increase the risk of herpes zoster and, consequently, the incidence of RHS. A 60-year-old woman presented with left-sided peripheral facial paralysis, otalgia, and vesicles on the ipsilateral auricle and external auditory canal. Laboratory tests and cranioencephalic computed tomography showed no significant acute changes. She was diagnosed with RHS and treated accordingly, subsequently showing a favorable evolution. Studies to date demonstrate the benefit of combined antiviral and corticosteroid therapy. Early treatment initiation, within the first 72 hours, is associated with a better prognosis and minimizes the risk of permanent neurological damage.